Japanese Encephalitis Virus-Induced Anti-N-Methyl-D-Aspartate Receptor Encephalitis: A Case Report and Review of Literature - Tian, Maoqiang; Li, Juan; Lei, Wenting; Shu, Xiaomei (Neuropediatrics, 2019)
Anti-N-methyl-D-aspartate receptor encephalitis (anti-NMDARe) was originally described as a paraneoplastic disease with more than 50% cases involving a tumor. However, tumor incidence in anti-NMDARe in children is much lower. Herpes simplex virus-induced anti-NMDARe has been well-described; however, findings on Japanese encephalitis virus (JEV)-induced anti-NMDARe are scarce. Here, we describe a 7-year-old boy who presented with fever and headache that progressed to seizures and disturbance of consciousness. Brain magnetic resonance imaging (MRI) revealed abnormalities in the bilateral globus pallidus. The diagnosis of JE was made based on a positive JE antibody test results in serum and cerebrospinal fluid. Antiviral and symptomatic therapies led to rapid recovery. Four weeks after the onset of JE, the patient presented with emotional and behavioral disturbances, sleep difficulty, and extrapyramidal symptoms. MRI showed symmetrical lesions in the bilateral thalami and basal ganglia which were expanded than those on the original scan. Antibodies against NMDAR were detected and immunotherapy led to significant recovery. This case and our literature review suggest that JEV may be a clinically important cause of anti-NMDARe in children. Patients with JE-induced anti-NMDARe present with symptoms similar to those of patients with primary anti-NMDARe. Most patients with JE-induced anti-NMDARe showed a good response to first-line immunotherapies.
Keywords: Japanese encephalitis; Japanese encephalitis virus; anti-NMDAR encephalitis; pediatrics